2016
DOI: 10.1063/1.4939585
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Configuration interaction combined with spin-projection for strongly correlated molecular electronic structures

Abstract: We present single and double particle-hole excitations in the recently revived spin-projected Hartree-Fock. Our motivation is to treat static correlation with spin-projection and recover the residual correlation, mostly dynamic in nature, with simple configuration interaction (CI). To this end, we introduce the Wick theorem for nonorthogonal determinants, which enables an efficient implementation in conjunction with the direct CI scheme. The proposed approach, termed spin-extended CI with singles and doubles, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 39 publications
1
64
0
Order By: Relevance
“…If all the EPV terms R ab ij are completely neglected, we obtain a large cancellation between the unlinked terms in Eq. (15). This is historically called CEPA(0), 29,46 and is equivalent to linearized CC theory (LCC).…”
Section: B Pair-energy and Several Approximationsmentioning
confidence: 99%
See 1 more Smart Citation
“…If all the EPV terms R ab ij are completely neglected, we obtain a large cancellation between the unlinked terms in Eq. (15). This is historically called CEPA(0), 29,46 and is equivalent to linearized CC theory (LCC).…”
Section: B Pair-energy and Several Approximationsmentioning
confidence: 99%
“…[17][18][19] The dynamical part of the correlation energy is then treated by either perturbation theory 12 or configuration interaction (CI). 15,16 Among these developments, it was shown that spin-extended CI with single and double substitutions (ECISD) can produce accurate results for systems where the static correlation plays an important role. The success of this method is a result of its effective MR-CI nature, which comes from the MC character of SUHF.…”
Section: Introductionmentioning
confidence: 99%
“…Thence, there is a big interest in combining both worlds, aiming at what is known as a black‐box description. Recently Tsuchimochi and Ten‐no have provided a very promising combination of the CI method and spin‐projection, specifically, they considered the spin projection of a singly and doubly excited UHF determinant: ΨECISDfalse〉=trueP^0.5em()|||c0normalΦfalse〉+IAcIAΦIAfalse〉+false∑I0.15em<-0.1emJA0.3em<0.1emB-0.5emcIJA0.2emBΦI0.6emJA0.33emBfalse〉. …”
Section: Spin‐extended Configuration Interactionmentioning
confidence: 99%
“…Besides our own efforts, [11][12][13] there have also been other attempts to combine SUHF with residual correlation methods. [40][41][42] In this work, we take a new approach, exploiting our recent formulation of SUHF for singlet states as a polynomial similarity transformation of particle-hole excitations out of a symmetry-adapted reference determinant. [11,13] Although some of the details of the PoST SUHF formulation are not key to this work, we need to establish that CC and SUHF can be written in a common language in order to justify modifying the CC equations based on the structure of the PoST SUHF equations.…”
Section: Projected Hartree Fockmentioning
confidence: 99%